Hisab Lima-Lima Sebagai Metode Penentuan Awal Bulan Ramadhan dan Syawal di Aceh Singkil dalam Kacamata Ilmu Falak - Rahmalia Rahmalia; Ahmad Izzuddin (Astroislamica: Journal of Islamic Astronomy, 2023)
Differences in determining the beginning of the Hijriyah month, especially the months of Ramadan and Shawwal, have become commonplace in Indonesia, the fasting of Ramadhan and Eid al-Fitr are not simultaneous, including in Aceh Singkil, people in the area use a calculation method known as Hisab lima-lima. This study aims to examine the hisab lima-lima method through the lens of astronomy by using qualitative research methods. Data were obtained from book sources, books, and interviews. The results of this study show that some of the people of Aceh Singkil in determining the beginning of the month of Ramadan and Shawwal still use the hisab lima-lima method, this method is a method from their ancestors, including Syekh Abdur Rauf As-Singkili. Hisab lima-lima is counting the first five days of Ramadan last year to determine fasting in the following year. In astronomy, hisab lima-lima is included in the hisab urfi which is based of the traditional calculation that the moon revolves around the earth for 354 days a year.